The Ranking of factors affecting the prediction of RES share in total energy consumption in Serbia: Multicriteria Analysis (ELECTE Method) - Tomic, Aleksandra (Industrija, 2026)
Apstrakt: The “Green Agenda” as a new global political and economic framework includes the gradual phase-out of coal by 2050 and a shift toward environmentally clean energy sources. This process, known as the energy transition, is driven by three key pillars: tackling climate change, protecting the environment, implementing energy efficiency measures, and integrating renewable energy sources (RES). Since Serbia has adopted a new National Energy Strategy and Energy and Climate Plan for 2040, this strategic framework has been incorporated into technical studies based on the country’s existing renewable energy potential.Every country must preserve the stability of its electricity system and energy security, while also maintaining economic and financial sustainability. This study presents a methodology for predicting the share of RES in total energy consumption using a multi-criteria mathematical model for ranking the most influential factors. A prediction model for the year 2030 is proposed, and the ranking of influencing factors reveals the limitations of individual variables and their interactions. Ranking factors affecting the prediction of the RES share involves a sequence of mathematical steps that describe the behavior of input variables such as meteorological conditions, types of days, electricity consumption, energy prices, and other characteristics. The model output is a ranked set of alternatives showing the expected RES share for the forecast period, based on projected consumption, climate variability, energy prices, technology development level, and global investment trends. The multi-criteria ELECTRE method demonstrated that the selected mathematical approach incorporates all variables, corrective coefficients, and weighting factors required to improve prediction reliability and accuracy. Such models have become mandatory components of energy development strategies worldwide for the period up to 2050.